Interpretação de pronomes sujeito anafóricos e catafóricos por falantes de português L2: efeitos da língua materna - Lobo, Maria; Madeira, Ana; Silva, Carolina (Revista da Associação Portuguesa de Linguística, 2020)
This paper investigates the interpretation preferences for null and overt subject pronouns in anaphoric and cataphoric contexts in L2 Portuguese and, specifically, whether: i) the L1 of the participants (Italian and German) influences their interpretation; ii) there is evidence of development; iii) there are differences determined by pronoun type and context. The results of a picture selection task administered to the L2 groups and a group of L1 adults show that the distinction between null and overt subjects is established early; learners distinguish anaphoric and cataphoric contexts and their performance may be influenced by processing constraints; there is some development from beginner to advanced level, visible in the Italian group mainly for overt pronouns; and the proximity of the L1 appears to facilitate L2 acquisition.